Giaccardi Inequality for s-Convex Functions in the Second Sense for Isotonic Linear Functionals and Associated Results - Dong Chen; Dina Abuzaid; Atiq Ur Rehman; Aqsa Rani (Journal of Mathematics)
In this paper, a well-known inequality called Giaccardi inequality is established for isotonic linear functionals by applying s-convexity in the second sense, which leads to notable Petrović inequality. As a special case, discrete and integral versions of Giaccardi inequality are derived along with the Petrović inequality as a particular case. In application point of view, newly established inequalities are derived for different time scales.